Application of the principles of universality and comprehensiveness in the treatment of rare diseases not supported by the Unified Health System (SUS) in Brazil - Angélica Silveira da Silva Moraes; Murillo Dias (Aposta: Revista de Ciencias Sociales, 2026)
Rare diseases are, by definition, pathologies that affect a small number of people but, together, profoundly impact a significant portion of the population and the health system. In Brazil, many of these diseases are not explicitly recognized in protocols or in the list of treatments offered by the SUS, which generates gaps in diagnosis, treatment, and social support. This research contributes to understanding how these gaps affect not only patients but also their families, the health system, and society in general. In addition, the study aims to highlight the ethical, social, and economic aspects that justify expanding support for these conditions, contributing to the debate on more equitable public policies aligned with the universal and comprehensive health defended by the Federal Constitution. By addressing this theme, the research seeks to collaborate with the strengthening of the right to health for all Brazilians, including those affected by rare diseases.